The educational image: towards a semiotic-didactic approach - bouzidi, ismail (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : I open up my work with the proverb that says: "No one has seen like someone heard" because we live in the age of the image, and the spread of visual culture. The visual image is a tangible and personalized representation of the world, different from the rhetorical image of perceived imaginative energy, because it is distinguished by its visual and semiotic nature 1) This means that the visual image is an iconic semiotic image Par excellence in which the signifier, the signified, and the reference are intertwined to form the relationship image, and it means that the visual image is a sensory image that addresses the eye more than it addresses the other senses and is related to shape, color, line, shadows, points, shape, state, impression, shot, light and wording ...We have set out from this introduction a problematic treatment of a cognitive and didactic nature Which :How do we teach language by image?.